2022
DOI: 10.1038/s41598-022-22570-w
|View full text |Cite
|
Sign up to set email alerts
|

Exercise serum regulates uric acid transporters in normal rat kidney cells

Abstract: Hyperuricemia (HUA) refers to a physiological condition of high serum uric acid (SUA) level in the body, which may cause an increased risk of several chronic diseases. The kidney’s impaired uric acid (UA) metabolism is an important reason for HUA. In this study, we tested the hypothesis that circulating factors produced during exercise regulate the expression of ABCC4, ABCG2, URAT1, and GLUT9 in normal rat kidneys and normal rat kidney cells (NRK-52E) and their relationship with NF-κB and NRF-2. NRK-52E cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Although the precise mechanisms by which EXE affects renal indicators are not fully understood, researchers have demonstrated that increasing subjects' aerobic capacity reduces their reliance on phosphoryl compounds with high energy-producing capabilities during physical activity [ 35 ]. This adaptation is associated with decreased adenosine monophosphate deaminase activity and reduced uric acid production [ 36 ]. Additionally, EXE can enhance kidney function by increasing nitric oxide availability, reducing oxidative stress, and elevating antioxidant levels in kidney tissue [ 14 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanisms by which EXE affects renal indicators are not fully understood, researchers have demonstrated that increasing subjects' aerobic capacity reduces their reliance on phosphoryl compounds with high energy-producing capabilities during physical activity [ 35 ]. This adaptation is associated with decreased adenosine monophosphate deaminase activity and reduced uric acid production [ 36 ]. Additionally, EXE can enhance kidney function by increasing nitric oxide availability, reducing oxidative stress, and elevating antioxidant levels in kidney tissue [ 14 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adaptation is associated with decreased adenosine monophosphate deaminase activity and reduced uric acid production [ 36 ]. Additionally, EXE can enhance kidney function by increasing nitric oxide availability, reducing oxidative stress, and elevating antioxidant levels in kidney tissue [ 14 , 36 ]. As a result, regular and continuous EXE adaptations can normalize blood urea, CR, and Alb levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Yi-Suan-Cha increased UA excretion by increasing ABCG2 expression and synergistically reduce UA with a variety of transporter proteins in vivo [ 36 ]. Moreover, blood circulating factors in rats after prolonged exercise dramatically enhanced the capacity of renal tubular epithelial cells to reabsorb UA via GLUT9 [ 37 ], and Sanghuangporus vaninii ethanol extract (SHEE) lowered uric acid through increasing renal OAT3 mRNA expression in HUA-treated mice [ 38 ]. Leech therapy increase the expression levels of GLUT9, ABCG2, and OAT3 in the rat kidney to control uric acid metabolism in some extents.…”
Section: Discussionmentioning
confidence: 99%
“…Lower blood urea levels indicate increased glomerular ltration and urea excretion through urine or decreased renal tubular reabsorption (52)(53)(54). Urea transport rate is determined by the electrochemical gradient for diffusion across the membrane and its permeability to the material (55). Furthermore, glomerular ltration depends on the negative charge of the podocyte basement membrane containing negatively charged molecules.…”
Section: Discussionmentioning
confidence: 99%